Antinociceptive and Anthelmintic Activities of Leaves of Leea aequata - Halder, Sushanta; Saqueeb, Nazmus; Qais, Nazmul (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The objective of the study was to evaluate the antinociceptive and anthelmintic activities of the crude methanol extract of leaves of Leea aequata and its fractions. The crude extract and its fractions at 200- and 400-mg/kg bw were subjected to assay for their antinociceptive activity using acetic acid induced writhing and radiant heat tail flicking methods. The ethyl acetate soluble fraction at 400 mg/kg bw induced 40.97% inhibition of writhing in mice while the carbon tetrachloride and chloroform soluble fractions of crude extract at the same dose displayed activity with 40.28% inhibition of writhing as compared to standard diclofenac sodium. The crude extract elongated the reaction time by 57.04% after 30 minute of administration in radiant heat tail flicking method, which suggested the central antinociceptive activity as compared to morphine. The methanol extract of the leaves of L. aequata exhibited profound anthelmintic activity in a dose dependent manner with shortest time of paralysis and death at 100 mg/ml concentration. It caused paralysis of the earthworm Pheretima posthuma at 9.44 min and death at 12.9 min when compared to the standard drug albendazole, which at 10 mg/ml concentration revealed the same at 8.21 minutes and 11.18 minutes, respectively. Dhaka Univ. J. Pharm. Sci. 17(2): 251-255, 2018 (December)